Effect of the Growth of MSMEs and Cooperatives Through Policies on the People's Economy - Fitriyah Ulfah; Daryono; Suchaina (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of the growth of Micro, Small, and Medium Enterprises (MSMEs) and cooperatives through public credit policies on the success of the people's economy. The background of this study is based on the strategic role of MSMEs and cooperatives in strengthening the national economy, but the effectiveness of public policy as a supporting factor still requires further study. The research method used is a quantitative method with a path analysis approach to examine the direct and indirect influences between variables. Data were obtained through a survey of MSME and cooperative actors who were the objects of the study. The results show that MSME growth has a significant direct influence on the success of the people's economy, while the indirect influence through public policy (credit) is insignificant. Meanwhile, cooperatives, either directly or through public policy, do not have a significant influence on the people's economy. These findings indicate that the success of the people's economy is still supported more by the growth of MSMEs than by cooperatives or government credit policies. In the future, similar research can expand its scope by including non-credit policy variables and a qualitative approach to provide a more comprehensive picture of the dynamics of the people's economy in Indonesia.